The Use of Solitaire AB Stents in Coil Embolization of Wide-Necked Cerebral Aneurysms - Li, Teng-Fei (PLoS One, 2015)
BACKGROUND: The Solitaire AB stent is one of many assistant stents used for treating wide-necked cerebral aneurysm, and has been used since 2003. However, large sample studies on its safety and effectiveness are lacking. The objective of this study was to evaluate the effectiveness and safety of the Solitaire AB stent in the coil embolization of wide-necked cerebral aneurysms. METHODS: Retrospective review of the clinical and image data of 116 patients with wide-necked cerebral aneurysms who had been enrolled at six interventional neuroradiology centers from February 2010 to February 2014 and had been treated by coil embolization; in total, 120 Solitaire AB stents were used. The degree of aneurysm occlusion was examined using digital subtraction angiography (DSA) immediately after the procedure and during follow-up, and was graded using the modified Raymond classification. We also observed complications to evaluate the safety and effectiveness of this therapy. RESULTS: The 120 Solitaire AB stents (4 mm × 15 mm, four stents; 4 mm × 20 mm, 16 stents; 6 mm × 20 mm, 36 stents; 6 mm × 30 mm, 64 stents) were inserted to treat 120 wide-necked cerebral aneurysms. All stents were inserted successfully. DSA immediately post-surgery revealed 55 cases of complete occlusion, 59 cases of neck remnant, and six cases of aneurysm remnant. Perioperatively, there were four cases of hemorrhage and four cases of stent thrombosis. The follow-up spanned 3–37 months; of 92 patients examined by DSA at the 6-month follow up, 12 had disease recurrence. CONCLUSIONS: The Solitaire AB stent is effective with a good technical success rate and short-term effect for assisting coil embolization of wide-necked cerebral aneurysms.